Non-Occlusive Bleeding Times May Improve the Value of Ivy Bleeding Times - Zeigler, Zella R (Thrombosis and Haemostasis, 1990)
The present studies measured bleeding times, without venous occlusion, in a series of patients, whose bleeding times (+ venostasis) consistently exceeded 20 min. During these tests, the amount of blood loss (expressed as mg/min) was also quantitated. To allow comparison, normal controls were studied before and following aspirin ingestion. In normal controls, the mean standard Ivy bleeding time was 5.0 with a range of 2.5 to 7.5 min. Two hours after aspirin (650 mg), this increased to 7.3 min (range 4.0−12.0). For comparison, the non-occlusive bleeding time averaged 3.8 min (1.0−6.5) and after aspirin 5.3 min (2.5−11.5). The measured amount of blood loss was 5.0 mg/min (0−10.5 mg/ min) under all of the above conditions. At the other extreme, patients with severe bone marrow failure had occluded and nonoccluded bleeding times in excess of 20 min. Moreover, these were often associated with excess blood loss. By contrast, patients with “Ivy” values >20 min in association with platelet counts >10,000/μl had unpredictable bleeding parameters. In the latter group, the non-occluded values ranged from 1 to >20 min. Of particular note, the non-occlusive times appeared to correlate with spontaneous bleeding manifestations. Only a rare patient (1/37), whose non-occluded value was <20 min, had worrisome bleeding. By contrast, serious bleeding manifestations were observed in 39% whose non-occluded value exceeded 20 min. This was even higher (64%) in those with a non-occluded value >20 min and excess blood loss. These studies provide laboratory and clinical evidence for the heterogeneous behavior of patients with venostasis bleeding times >20 min. These additional laboratory measurements may be helpful in defining risk of spontaneous bleeding and in evaluating therapeutic strategies in such patients. However, studies will need to be performed to correlate this type of information with bleeding associated with invasive diagnostic or surgical procedures.